Masalah Emosi dan Perilaku Remaja di SMPN 77 Jakarta Pusat - Giri Widakdo; Naryati Naryati; Nuraenah Nuraenah; Aisyah Aisyah; Hirfaturrahmi Hirfaturrahmi; Mokhamad Arifin; Agniatul Mahmudah; Ajeng Putri Rahmawati (Malahayati Nursing Journal, 2025)
ABSTRACT Emotional and behavioral problems in adolescents are critical issues that impact the well-being of individuals and society. The prevalence of mental disorders in adolescents globally reaches 10-20%. This study aims to identify emotional and behavioral problems of adolescents at SMPN 77 Central Jakarta using the Strengths and Difficulties Questionnaire (SDQ). The design of this study was cross-sectional with 264 respondents aged 11-17 years. Results showed the majority of respondents were in the “Normal” category. However, females were more likely to be in the abnormal category on emotional problems (33.1%) than males (13.9%), while males were more in the borderline category on behavioral problems (19.7%). These findings suggest the importance of early intervention to address emotional and behavioral problems in adolescents. Keywords: Adolescents, Emotion, Behavior, SDQ  ABSTRAK Masalah emosi dan perilaku pada remaja adalah isu kritis yang berdampak pada kesejahteraan individu dan masyarakat. Prevalensi gangguan mental pada remaja secara global mencapai 10-20%. Penelitian ini bertujuan mengidentifikasi masalah emosi dan perilaku remaja di SMPN 77 Jakarta Pusat menggunakan Strengths and Difficulties Questionnaire (SDQ). Desain penelitian ini adalah cross-sectional dengan 264 responden usia 11-17 tahun. Hasil menunjukkan mayoritas responden berada dalam kategori "Normal." Namun, perempuan lebih cenderung masuk kategori abnormal pada masalah emosional (33.1%) dibandingkan laki-laki (13.9%), sementara laki-laki lebih banyak dalam kategori borderline pada masalah tingkah laku (19.7%). Temuan ini menunjukkan pentingnya intervensi dini untuk menangani masalah emosi dan perilaku pada remaja Kata Kunci: Emosi, Perilaku, Remaja, SDQ